2016
DOI: 10.1002/imhj.21568
|View full text |Cite
|
Sign up to set email alerts
|

Parental Regulation of Infant Sleep: Round-the-Clock Efforts for Social Synchronization

Abstract: The sleep-cycle development of infants is influenced by familial and sociocultural conditions, but there is a lack of knowledge on how parental regulation of infant sleep is related to the specific life situation of a family. This article describes a context-sensitive study of parental regulation of infant sleep that includes the whole 24-hr day, parents' intentions, and familial and sociocultural conditions. The results are based on a longitudinal qualitative study in Norway of 51 families. Parents were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…A transactional sleep framework acknowledges multiple influences on infant sleep development, such as environmental (including health promotion guidelines), cultural (including sleep location), and infant and parental factors (including beliefs, temperament, and choice), meaning approaches that can be tailored to individual families may ultimately have more appeal and increased adherence and use than one-size-fits-all guidelines. 44 The current pilot study was necessarily limited by size. Ethnically and demographically similar groups of women were targeted for participation to control those factors.…”
Section: Discussionmentioning
confidence: 99%
“…A transactional sleep framework acknowledges multiple influences on infant sleep development, such as environmental (including health promotion guidelines), cultural (including sleep location), and infant and parental factors (including beliefs, temperament, and choice), meaning approaches that can be tailored to individual families may ultimately have more appeal and increased adherence and use than one-size-fits-all guidelines. 44 The current pilot study was necessarily limited by size. Ethnically and demographically similar groups of women were targeted for participation to control those factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, increasing the interval before feeding as infants aged was the General-Community parents’ most common longitudinal parenting strategy, suggesting that parents who implemented this from birth adopted a form of parenting which is normative as infants grow older. Evidence that parenting typically becomes less infant-cued as infants age has been found, too, in other English (Williams et al ., 2016 ) and Norwegian (Sudnes and Andenaes, 2016 ) studies. It seems likely that parents’ initial concern about their baby’s well-being and weight gain gives way to a more deliberated approach as infants develop.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both infra-red video recordings and most randomised controlled trials have found that ‘limit-setting’ parenting supports both breast and formula-fed infants in developing long night-time sleep periods [43]. ‘Limit-setting’ parenting—an approach which employs routines and delayed responding to encourage infants to develop autonomous settling— is common in western societies and increasingly adopted by parents in general as infants grow older, at least in Norwegian [47] and English [48] families. A provocative idea, supported by correlational evidence, is that some parents’ unwillingness to tolerate crying leads to excessive involvement in soothing their infants to sleep, which gives rise to the development of sleep problems [49].…”
Section: Adult Responses To Infant Cryingmentioning
confidence: 99%